Chad : Fifth Review under the Extended Credit Facility Arrangement and Financing Assurances Review-Press Release; Staff Report; Staff Supplement; and Statement by the Executive Director for Chad. (IMF Staff Country Reports; Country Report, 2020)
This paper highlights Chad's Fifth Review Under the Extended Credit Facility (ECF) Arrangement and Financing Assurances Review. Chad's performance under the Fund's ECF-supported program has been broadly satisfactory, reflecting strong commitment by the authorities despite a challenging environment, including security concerns and a tense social situation. Good progress on the structural reform agenda has been made, despite some delays. Looking ahead, it is essential that the authorities continue to pursue prudent fiscal policy, particularly in the run up to the upcoming elections, create enough fiscal space for increased social and development spending, and pay down domestic debt and arrears. Chad's program is supported by the implementation of supportive policies and reforms by the regional institutions in the areas of foreign exchange regulations and monetary policy framework and to support an increase in regional net foreign assets, which are critical to the program's success.